Half-Effect Applied to Equidistance Lines - Beazley, P. B. (The International Hydrographic Review, 2015)
Two continental shelf delimitations have specified that an island or islands should be given only half-effect, but the concept has been applied in different ways. This paper examines some ways in which, assuming the case to be appropriate, half-effect may be applied, and demonstrates the need to consider carefully what modification to the equidistance line is intended before deciding on the method to use. The views expressed in this article are those of the author, and do not necessarily reflect those of the British Government.